A comparative study of neoadjuvant treatment with gemcitabine plus nab-paclitaxel versus surgery first for pancreatic adenocarcinoma. (December 2017) - Ielpo, Benedetto; Caruso, Riccardo; Duran, Hipolito; Diaz, Eduardo; Fabra, Isabel; Malavé, Luis; Ferri, Valentina; Alvarez, Rafael; Cubillo, Antonio; Plaza, Carlos; Lazzaro, Sara; Kalivaci, Denis; et al.
Abstract: Introduction: Neoadjuvant treatment has been reported to prolong survival in patients with potentially resectable pancreatic adenocarcinoma (PA). However, there are currently limited clinical results available using nab-paclitaxel and gemcitabine in PA. This paper compares the oncological results of patients affected by potentially resectable PA who underwent surgery first (SF) versus surgery following neoadjuvant treatment (NAT). Methods: This is an observational, comparative study whereby data were abstracted from a prospective database of patients affected by PA from 2007 to 2016. Results: We included a total of 81 patients (36 SF and 45 NAT) which resulted in being preoperatively similar. Among the NAT patients, treatment was well tolerated and the resection rate was 68.8% (31/45 patients). There was a trend towards a higher R1 resection rate in the SF group compared with the NAT (13.8% vs 3.2%; p = 0.1). Median overall survival in the resected NAT group was higher (30.6 vs 22.1 months; p = 0.04). In the borderline resectable group, overall survival was found to be four times higher compared with SF (43.6 versus 13.5 months; p = 0.001). Conclusions: These data suggest that neoadjuvant treatment with gemcitabine/nab-paclitaxel is a safe and effective option for potentially resectable PA compared with the SF approach. Abstract : This study compares early and late post-operative outcomes of patients affected by pancreatic adenocarcinoma which underwent traditional upfront surgery approach versus surgery after novel gemcitabine-/nab-paclitaxel based neoadjuvancy.